Men who Care: men’s motivations in taking up positions in community mobilisation organizations in Gugulethu to improve the public healthcare system - Malunga, Samantha (Department of Public Health and Family Medicine, 2019)
Many men in South Africa (SA) want to participate in improving their community. Having lived in the community, they are more attuned to the immediate needs of the community - and male members of the community’s needs in particular - compared to NGOs or external support systems that may try do social development work in SA. There is a great opportunity to include more men in community mobilisation (CM) work and health systems strengthening programs in SA and beyond. Historically, volunteer work, including CM has been seen as a job for women. There are fewer male volunteers in CM than there are female volunteers; hence, more research has been conducted around female volunteers’ experiences and motivations. In order to support the greater inclusion of men in volunteer work, this mini-dissertation explores men’s motivations to participate in CM work. This mini-dissertation is divided in the following three parts. A research protocol (Part A) which focuses on understanding the motivations of male community mobilisers who are involved in activist community work in the Gugulethu Township. A literature review (Part B) which examines existing literature on volunteer work and how gender affects experiences of, and motivations to volunteer. Lastly, a manuscript for Social Dynamics (Part C) that focuses on the gendered experiences and motivations of men who participate in CM work in the Movement for Change and Social Justice (MCSJ), a community organisation in Gugulethu, Cape Town. The knowledge gained from this mini-dissertation can feed into the larger debate present in SA surrounding the need for more male-centred interventions in the public healthcare system and aims to show how the visibility and representation of male volunteers in the health system can have a positive impact on men’s health seeking behaviours in communities through increasing their linkage to and retention in care.